Effects of supplementation strategies during the growing phase on meat quality of beef cattle finished in different systems - Torrecilhas, Juliana Akamine [UNESP]; San Vito, Elias; Fiorentini, Giovani; Castagnino, Pablo de Souza [UNESP]; Simioni, Tiago Adriano [UNESP]; Lage, Josiane Fonseca; Baldi, Fernando [UNESP]; Duarte, Juliana Messana [UNESP]; Silva, Lorrayny Galoro da [UNESP]; Reis, Ricardo Andrade [UNESP]; Berchielli, Telma Teresinha [UNESP] (Elsevier B.V., 2021)
One hundred and twenty bulls were used in a randomized complete block design in 2 ? 2 factorial arrangement; two supplements during the growing phase: mineral (ad libitum; MIN) or protein + energy [0.3% of body weight (BW)/animal/day; PRE] and two finishing systems: pasture plus concentrate supplementation (2% BW/animal/ day; PASCO) and feedlot (25:75% corn silage:concentrate; FLOT). The supplementation strategy at growing phase did not affect (P 0.050) the pH, shear force, sarcomere length and myofibrillar fragmentation index of the animals. Backfat thickness was increased and meat shear force was decreased (P < 0.050) when the bulls were finished in FLOT. Bulls from PASCO presented an increase (P < 0.050) in the yellowness subcutaneous fat and myoglobin concentration, and a decrease in L* and a* values in meat during storage days. Meat lipid oxidation was decreased (P < 0.011) in bulls fed MIN during the growing phase followed by PASCO. Supplementation used at growing phase did not affect the meat quality of the bulls and the feedlot system slightly improved beef tenderness and colour compared to pasture plus supplementation.
Keywords: Intensive system; Longissimus thoracis; Meat quality; Tenderness traits